2015
DOI: 10.1111/1759-7714.12298
|View full text |Cite
|
Sign up to set email alerts
|

Response to crizotinib in a squamous cell lung carcinoma patient harbouring echinoderm microtubule‐associated protein‐like 4‐anaplastic lymphoma translocation: A case report

Abstract: Squamous cell lung cancer (SCC) presenting with anaplastic lymphoma kinase (ALK) translocation is rare. We present a case of ALK gene translocation‐SCC in which a remarkable tumor response to crizotinib was achieved after the failure of prior chemoradiotherapy. Considering this remarkable response, we conclude that ALK testing in female non‐smokers or in any patient unresponsive to the initial regimen of chemotherapy, is recommended for SCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Three patients 12,19,20 diagnosed with stage III SCC underwent radiation therapy. After regular check‐ups, one patient was confirmed to have recurrent disease, and underwent treatment with crizotinib.…”
Section: Resultsmentioning
confidence: 99%
“…Three patients 12,19,20 diagnosed with stage III SCC underwent radiation therapy. After regular check‐ups, one patient was confirmed to have recurrent disease, and underwent treatment with crizotinib.…”
Section: Resultsmentioning
confidence: 99%
“…Some patients with ALK-positive Sq-LC who were never smokers or light ex-smokers responded to crizotinib and showed a PFS longer than 5.8 months [ 22 26 ]. However, even these temporary responders to crizotinib showed shorter PFS than those in previous clinical trials of ALK-rearranged Ad-LC (PROFILE1007: 7.7 months and PROFILE1014: 10.9 months).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1, only 10 cases of ALK-rearranged LSCC treated with ALK inhibitors, including crizotinib, ceritinib, and alectinib, have been reported in the literature to date (5,(9)(10)(11)(12)(13)(14)(15)(16)(17). In these few studies, only one reported co-mutation of ALK and RoS1 double-rearrangement (5).…”
Section: Discussionmentioning
confidence: 99%